The impact of electronic commerce on the Peruvian firms' revenue - Ruiz Hurtado, Lysbeth Mishel (2022)
Electronic commerce is a way of sale that has come to stay. It helps companies to overcome physical barriers, and in theory, it increases their sales. However, does electronic commerce have any impact on the firms' revenue? This research sought the answer by employing OLS and quantile regressions in a sample of 2164 Peruvian retail firms. The dataset was obtained through the INEI economic survey of 2019, which was the last one. For methodological purposes, electronic commerce was compared against the other sales channels employed by the studied firms. It was found that electronic commerce positively impacted the income in firms with more enormous revenues but was still low compared with traditional commerce forms.